Personality Disorders and Correlates of Homicide Offenders: A Comparative Analysis - Armiya’u, Aishatu Yusha’u (The journal of forensic psychiatry & psychology, 2021)
Homicide is one of the most severe crimes in the criminal justice system. Evidence shows that the majority of offenders are likely to have a mental disorder. Studies have established a relationship between personality disorders, substance use and violence among offenders. The need to understand the concept of personality disorders related to homicide and non-homicide offending cannot be over-emphasized in low-and-middle-income countries. This study compared personality disorders, substance use, and correlates between homicide and non-homicide offenders. Faschingbauer’s Abbreviated Minnesota Multiphasic Personality Inventory (FAM) was used. Personality disorders were identified in a comparative study involving 204 homicide and non-homicide offenders in a Nigerian prison. Results indicated that paranoid personality disorder was prevalent among homicide offenders while antisocial personality disorder was prevalent among non-homicide offenders. The highest percentage of substance use was related to opioids among non-homicide offenders. The study helps to understand the importance of psychiatric assessment, mental health services and treatment options for offenders in custody.